ANALISIS FAKTOR RELIGIOSITAS, PENGETAHUAN EKONOMI SYARIAH, DAN MOTIVASI INVESTASI TERHADAP MINAT INVESTASI SAHAM SYARIAH PADA MAHASISWA AKUNTANSI (Studi Kasus Pada Mahasiswa Akuntansi Di Kota Malang) - Dita Dwi Lestari; M. Cholid Mawardi; Hariri Hariri (Universitas Islam Malang, 2022)
This study was conducted to determine the effect of religiosity factors, knowledge of Islamic economics, and investment motivation on interest in Islamic stock investment in accounting students. This research was conducted on accounting students class 2018 at the University of Islam Malang, Maulana Malik Ibrahim State Islamic University and the University of Muhammadiyah Malang who have customer fund accounts (RDN). The sampling method was a purposive sampling order to obtain a sample of 100 respondents who had met the sample criteria. In this study using multiple linear regression analysis methods using the SPSS 16.0 application as an analytical tool in this study. The results showed that the religiosity variable partially had a positive and significant effect on interest in Islamic stock investment. The variable knowledge of Islamic economics partially has a positive and significant effect on interest in Islamic stock investment. The investment motivation variable partially has a positive and significant effect on the interest in Islamic stock investment. The variables religiosity, knowledge of Islamic economics, and investment motivation together have a significant effect on interest in Islamic stock investment. Keywords: Religiosity, Islamic Economics, Investment, Motivation, Islamic Stock